The Impact of Mangrove Destructi The Impact of Mangrove Destruction on the Economy and Advocacy Efforts for Mangrove Conservation in Indonesia - Zainal Arifin; Andi Yusapri; Arief Rachman. B; Suherman Suherman; Bambang Sasmita Adi Putra (Cita Konsultindo Research Center, 2023)
This research delves into the multifaceted impact of mangrove destruction on Indonesia's economy and examines advocacy initiatives for mangrove conservation, employing a qualitative literature review methodology. The primary objective is to comprehensively understand the economic consequences of mangrove degradation, especially in coastal communities highly dependent on mangrove ecosystems. This study positions itself within the existing research on environmental degradation and its socioeconomic ramifications, with a particular focus on mangroves. The research involves an extensive review of qualitative literature sources, including academic articles, reports, and case studies. The main findings highlight the significant economic losses incurred due to mangrove destruction and emphasize the urgency of conservation efforts. Additionally, this study contributes to the body of knowledge by shedding light on the complex interplay between environmental degradation and economic vulnerabilities in coastal regions, underscoring the need for sustainable policies and community engagement in mangrove conservation.